If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-2=-4+8x
We simplify the equation to the form, which is simple to understand
6x-2=-4+8x
We move all terms containing x to the left and all other terms to the right.
+6x-8x=-4+2
We simplify left and right side of the equation.
-2x=-2
We divide both sides of the equation by -2 to get x.
x=1
| 2y=0+4 | | 2(0)=x+4 | | 7z+3=9z-3z | | 3x^2+6x=-10 | | 145.6+84.56-37.384= | | 3(0)-6y=6 | | x^2-6x-130=0 | | x^2-5x-130=0 | | 7x-2(-14)=14 | | 7x-2(0)=14 | | 7(0)-2Y=14 | | -2.3n+12=21 | | 11=[3x+5] | | 4y+5=y+26 | | 6(2-x)=9-2x+4+3x | | -7(p+7)+3(p-4)=-17 | | -4x+14=0 | | -5b+4=18 | | -4(x-y+8)= | | -14+n=-6 | | 5x-5=4x+23 | | -3a-7=2.3 | | 6x+6+13x+3=180 | | 1=X-.515 | | -(-2t)= | | .02X=.04 | | X-16=.08 | | 8v^6-18v-30=0 | | 3v^3+5v^2-18v-30=0 | | X-6=.48 | | 7+2x=2.5+.5x | | X+6=.52 |